2008
DOI: 10.1093/jpepsy/jsn108
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: A Web-Based Mental Health Program: Reaching Parents at Work

Abstract: Findings suggest that referring parents to a multimedia web-based program can improve parents' knowledge of children's' mental health and their confidence in addressing mental health issues. Web-based programs can be offered to individuals in multiple settings, including the workplace, thereby reaching large numbers of parents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(76 citation statements)
references
References 23 publications
3
73
0
Order By: Relevance
“…Consistent with previous research (Dietz et al, 2009), the intervention workshop increased parents' knowledge of depression and anxiety. Moreover, the current intervention focused on distinguishing between symptoms and normal teenage behavior, a need reported by parents previously (Hurley et al, 2017).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Consistent with previous research (Dietz et al, 2009), the intervention workshop increased parents' knowledge of depression and anxiety. Moreover, the current intervention focused on distinguishing between symptoms and normal teenage behavior, a need reported by parents previously (Hurley et al, 2017).…”
Section: Discussionsupporting
confidence: 83%
“…The qualitative investigation indicated that brief (single session) interventions can benefit parents and adolescents. In another study, an educational online program for parents delivered in the workplace sought to educate parents on depression and anxiety and help seeking services (Dietz et al, 2009). It was found that parents using the website improved their mental health knowledge and confidence to handle mental health issues to a greater extent than participants in a waitlist control condition.…”
mentioning
confidence: 99%
“…Based on consensus of the two coders, 11 studies were selected for full evaluation. Four studies were excluded because the intervention was not parenting training (Buzhardt & Heitzman‐Powell, ; Deitz, Cook, Billings, & Hendrickson, ; Na & Chia, ; Pacifici, Delaney, White, Nelson, & Cummings, ) and the fifth study was not included because the paper did not present original research, but rather described how technology can reduce barriers to dissemination of interventions for parents and adolescent children (Gordon, ).…”
Section: Methodsmentioning
confidence: 99%
“…A variety of technology-assisted parenting interventions have emerged in the field of early childhood, ranging from universal programs for new parents to indicated interventions targeting various child difficulties, including attention deficit-hyperactivity disorder (Deitz, Cook, Billings, & Hendrickson, 2009; Reese, Slone, Soares, & Sprang, 2012), traumatic brain injury (Antonini et al, 2014), and fetal alcohol spectrum disorders (Kable, Coles, Strickland, & Taddeo, 2012), among others. A variety of technology tools are applied in these programs, including the use of the internet to deliver information, the use of online discussion forums to improve parent social support networks, the use of mobile phones or texts for brief interventions or to enhance interventions, the use of video teleconferencing to connect providers and parents, and multi-component or hybrid models that blend different forms of technology use and face-to-face intervention delivery.…”
Section: Potential Of Technology To Improve Reach and Impact Of Parenmentioning
confidence: 99%